A kinematic study on the dive-in behaviour during swim start performance from the block - Fischer, S.; Kibele, A. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: While dive-in performance after swim start from the block is considered to be essential for swim start performance in general (e.g. Bonnar, 2001; Guimaeres & Hay, 1985), there are only few studies in the literature related to an examination of underwater kinematic profiles in elite swimmers. This deficit might be due to apparent methodological problems involved when detecting body landmarks as air particles swept along the body surface distorting a clear vision. A new procedure was developed to identify body landmarks despite visual restrictions during the dive-in phase. A study was conducted to examine the kinematic differences in elite swimmers. METHOD: Sixteen male elite swimmers participated in the study. Starting performance was studied in the course of a 50m speed test and measured by the time elapsed between the starting signal and the passage of the head at 7,5 m. Three video cameras were used for data acquisition. While block performance and head passage at 7,5 m were analyzed by two above water cameras, an under water video system was used to examine the dive-in behaviour. Since body landmarks are hard to be identified because of air particles carried along the body surface during dive-in, segment mid-lines were evaluated by a linear regression model (Fischer & Kibele, 2007). Traditional body landmarks (segment end-points) were identified as intersections of two adjacent segment mid-lines. RESULTS: Significant statistical correlations were found between the starting performance and the hip angle at water entry of the centre of mass (r=-0.72**), the mean horizontal velocity during the dive-in phase (r=-0.72**), and the maximal dive-in depth (r=-0.69**). Accordingly, significant differences in these parameters were found between good starters and poor starters. No differences were found in the mean horizontal velocity between starting signal and water entry, angle of the centre of mass trajectory at first water contact. There are indications that good starters minimize their loss in horizontal velocity during dive-in by the use of a dolphinkick. Moreover, good starters perform deeper dives during the transition to the horizontal body position. Our results indicate, that good starters also show higher angular impulses about the transverse body axis.